Secure and Privacy -Preserving Data Access Management IOD Systems in Distributed Cloud Networks - Chivukula Venkata Sai Saketh Ram; Mr. S. Ramesh (Utilitas Mathematica, 2025)
The emerging combination of Internet of Things (IoT) and 6G communication techniques has stimulated the Internet of Unmanned Aerial Vehicles (UAVs), i.e., Internet of Drones (IoD). To accommodate and share the enormous real-time UAV data, Cloud-based IoD is an inevitable choice to lower the heavy burden of mobile UAVs. Nevertheless, how to protect highly sensitive UAV data in such a honest-but-curious, open and distributed environment with resource-limited UAVs is a significant challenge. Although our previous work (PATLDAC) in SPNCE’21 devises a cloud-based UAV data access control scheme with policy privacy protection, limited access time and user traceability, it incurs inflexible and centralized cloud data storage and access as well as untrustworthy metadata in untrusted cloud environment for data access and user tracing. To this end, we further propose a blockchain-based privacy-aware data access control (BPADAC) scheme for distributed and secure UAV data sharing in Cloud-based IoD. Based on fine-grained, traceable and privacy-preserving UAV data access characteristic of our previous work, we extend it by leveraging blockchain and Distributed Hash Table (DHT) for distributed and trustful UAV data access and storage, together with reliable and limited access mechanism to guarantee cloud UAV data sharing service provision. We also design public and undeniable user tracing mechanism to prevent user key abuse with traitor denial.